2020
DOI: 10.1111/sdi.12861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal replacement therapy modalities on renal recovery and mortality for acute kidney injury: A PRISMA‐compliant systematic review and meta‐analysis

Abstract: Previous investigations showed inconsistent results for comparison in renal recovery, in‐hospital, and in‐intensive care unit (ICU) mortalities between acute kidney injury (AKI) patients treated with continuous renal replacement therapy (CRRT) and some kinds of intermittent renal replacement therapies (IRRTs). We systematically searched for articles published in the databases (PubMed, Web of Science, EMBASE, Medline, and Google Scholar) until June 2019. We made all statistical analysis using STATA 12.0 softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…With the exception of one small-sized study of 70 participants [21], most studies included in this review involved about 200 critically ill patients and had high mortality rates of more than 50%. A recent meta-analysis reported that AKI patients who received CRRT had a 21% higher in-ICU mortality than patients with intermittent hemodialysis [48]. Despite this, very few studies have examined the relationship between CRRT and in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of one small-sized study of 70 participants [21], most studies included in this review involved about 200 critically ill patients and had high mortality rates of more than 50%. A recent meta-analysis reported that AKI patients who received CRRT had a 21% higher in-ICU mortality than patients with intermittent hemodialysis [48]. Despite this, very few studies have examined the relationship between CRRT and in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Pajewski and colleagues supported the findings that a higher proportion of patients on CKRT had a better chance of kidney recovery (71.4% vs. 31.4%) in comparison to IHD [70]. On the other hand, other studies failed to show a significant difference in AKI outcome among different dialysis modalities on kidney recovery [23,80,[82][83][84][85][86][87].…”
Section: Outpatient Care Of Patients With Aki-d 241 Dialysis-related Factors Renal Replacement Modalitymentioning
confidence: 91%
“…Our updated literature search identified no new RCTs but two meta-analysis comparing continuous and intermittent renal replacement therapies [ 503 , 504 ]. The quality of evidence was judged as low.…”
Section: Additional Therapiesmentioning
confidence: 99%